UV curing formulations with high RI for microlenses - Choo, Paul Li Tze. (2011)
This project is about the investigation of prospective high refractive index (RI) polymer materials for use in graded refractive index (GRIN) microlens. An aliphatic polyurethane diacrylate was combined with three different zirconium acrylates containing one, two or three acrylate groups in different weight compositions and subjected to differential photocalorimetry (DPC) analysis to derive the specific rate co-efficient and induction time of each formulation to determine the viability of the materials for making microlens via ultraviolet (UV) embossing. It is also proposed to determine the RI of all formulations as it is a critical material value for graded index microlens. Unfortunately, the latter experiments could not be carried out due to circumstances that occurred after the commencement of the project. Nevertheless, discussions on the results obtained in the former part of the project as well as subsequent recommendations will be touched upon in this project. Actual design and fabrication of the microlens is beyond the scope of this project.